Probiotics mitigate stress and inflammation in malnourished adults via gut microbiota modulation: a randomized controlled trial - Ahmadi-Khorram, Maryam; Hatami, Alireza; Asghari, Parastoo; Jafarzadeh Esfehani, Ali; Afshari, Asma; Javdan, Fateme; Nematy, Mohsen (Frontiers in Nutrition, 2025)
ObjectiveMalnutrition negatively affects mental health by altering neurotransmitter function and increasing stress responses. The gut-brain axis is pivotal in this process, and probiotics may mitigate stress. The current study examined the effects of multi-strain probiotic supplementation on stress levels in underweight individuals using the Perceived Stress Scale (PSS).MethodsA double-blind, randomized, placebo-controlled trial involved 100 underweight participants were randomized to receive either a probiotic supplement (Lactobacillus acidophilus, L. casei, L. rhamnosus; 3 × 109 CFU) or placebo for 8 weeks. Stress levels, anthropometric measures, and inflammatory markers (ESR, CRP) evaluated at baseline and post-intervention.ResultsNinety participants (mean age: 26.22 ± 7.42 years) completed the study (probiotic: n = 47; placebo: n = 43). Baseline age (p = 0.051) and gender (p = 0.101) showed no significant differences. Post-intervention, the probiotic group exhibited significant weight increases (p = 0.005), waist circumference (p = 0.038), and hip circumference (p = 0.008), and a significant reduction in Perceived Stress Scale (PSS) scores (p < 0.001) in comparison to the placebo. Inflammatory markers (ESR, CRP) also decreased significantly in the probiotic group (p < 0.001). Within-group analysis revealed improvements in anthropometric measures and inflammatory markers in both groups (p < 0.05), but stress reduction was more pronounced in the probiotic group (34% vs. 9.3%, p = 0.017). A significant time-group interaction was observed for stress scores (p < 0.001).DiscussionThe findings suggest that probiotic supplementation reduces stress levels in underweight individuals, possibly through gut microbiota modulation and inflammation reduction. Further research with larger samples and microbiome analysis is warranted.ConclusionIn conclusion, administering probiotics to underweight patients positively impacts their mental health and exhibits anti-inflammatory effects.Clinical trial registrationhttps://irct.behdasht.gov.ir/trial/69130, identifier IRCT20230310057667N1.